Redesign Line Drain Pada Filter Heat Exchanger PLTU Indramayu - Andika Widya P; Mae Nitto Budi Karsono (JURNAL POWERPLANT, 2014)
The use of electricity in modern life today is a necessity and demands that can not be separated from everyday activities. Indramayu power plant which has a capacity of 3 x 330 MW is one of the coal-fired thermal power plant that supplies the system interconnect JAMALI (Java, Madura, Bali). Thus generating performance reliability is a must. In the production process kapaitas Indramayu with 3 x 300 MW, there are many tools that support to optimize the power production process, whether it is the main equipment and auxiliary equipment. The main equipment at this plant, among others such as boilers, turbines, generators and condensers. Indramayu contained cooling water cycle that serves to cool the various systems, for example: as a generator coolant, lube oil coolers, etc. In the cooling water cycle, there are a medium for transferring heat from a hot medium into a cold media, the tool is called Heat Exchanger (HE) .Heat discussed exchanger using sea water cooling medium, so it is prone to dirty / clogged. Therefore, before entering the heat exchanger there is a filter called debris filter Heat Exchanger. In pengoprasian debris filter Heat Exchanger there are many obstacles, one of which is the overflow of water in the sump tank which would cause flooding on the ground floor and the matter will be discussed in this project so that it does not reoccur.